A new species of Swertia L. (Gentianaceae) from Eastern Himalaya, India - Lepcha, Dharmit; Singh, Harsh; Hajong, Bipankar; Chettri, Arun (Phytotaxa, 2025)
Swertia nectariconnatus is described as a new species from Tara Dho, Myong, North Sikkim, India. This new species resembles its congeneric Swertia pseudohookeri, but it differs by the rhomboid calyx lobes, paired, fused, ovate shaped nectaries located at the base of the corolla, bifid at the apex and greenish-black in colour, and carpel ellipsoid with a bifid apex. Illustrated plates with coloured photographs and a distribution map are provided.